A Norwegian prospective study of preterm mother–infant interactions at 6 and 18 months and the impact of maternal mental health problems, pregnancy and birth complications. Issue 5 (4th May 2016) - Misund, Aud R; Bråten, Stein; Nerdrum, Per; Pripp, Are Hugo; Diseth, Trond H
Abstract : Objective: Pregnancy, birth and health complications, maternal mental health problems following preterm birth and their possible impact on early mother–infant interaction at 6 and 18 months corrected age (CA) were explored. Predictors of mother–infant interaction at 18 months CA were identified. Design and methods: This prospective longitudinal and observational study included 33 preterm mother–infant (<33 gestational age (GA)) interactions at 6 and 18 months CA from a socioeconomic low-risk, middle-class sample. The Parent–Child Early Relational Assessment (PCERA) scale was used to assess the mother–infant interaction. Results: 'Bleeding in pregnancy' predicted lower quality in preterm mother–infant interaction in 6 PCERA scales, while high 'maternal trait anxiety' predicted higher interactional quality in 2 PCERA scales and 'family size' predicted lower interactional quality in 1 PCERA scale at 18 months CA. Mothers with symptoms of post-traumatic stress reactions, general psychological distress and anxiety at 2 weeks postpartum (PP) showed significantly better outcome than mothers without symptoms in 6 PCERA subscales at 6 months CA and 2 PCERA subscales at 18 months CA. Conclusions: Our study detected a correspondence between early pregnancy complications and lower quality of preterm mother–infant interaction, and an association between high levels of maternal mental health problems and better quality in preterm mother–infant interaction.